ANALISIS PENGARUH JUMLAH PENDUDUK MISKIN, PENGELUARAN PEMERINTAH BIDANG KESEHATAN DAN BIDANG PENDIDIKAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI RIAU - Christin, Silaban Natalia; Harlen, Harlen; Lapeti, Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of factors of the number of poor people, government spending in health and education in the human development index in Riau Province. This study uses secondary data in the form of annual time series data from 2010-2018. The analytical method used is multiple linear regression, statistical testing includes the f test, t test, and R square (coefficient of determination), as well as the classic assumption test that is normality, multicollinearity, autocorrelation and heteroscedesticity with the help of SPSS 24.0. From the results of this study it was found that the variable number of poor people, government spending in health and education simultaneously had a significant effect on the human development index in Riau Province. While partially the number of poor population (X1) in this study significantly influenced the human development index. For government expenditure variables in health (X2) and education (X3) no significant effect on the human development index. The magnitude of influence caused (R2) by these three variables together to the dependent variable is 60.4% while the remaining 39.6% is influenced by other variables not included in this study.Keywords: Human Development Index, Government Spending in Health and Education